2017
DOI: 10.1111/ajo.12609
|View full text |Cite
|
Sign up to set email alerts
|

General practitioners and preconception weight management in New Zealand

Abstract: General practitioners in NZ are not providing optimal preconception care. This research highlights the need for a public health message encouraging preconception counselling and better education of GPs on the topic. This should start with promotion of the Ministry of Health guidance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…Obstetric care providers . Certified obstetricians and gynecologists, general practitioners, integrated emergency surgical officers, nurses, midwives, and public health officers working in maternal and reproductive health care units [ 16 ].…”
Section: Methodsmentioning
confidence: 99%
“…Obstetric care providers . Certified obstetricians and gynecologists, general practitioners, integrated emergency surgical officers, nurses, midwives, and public health officers working in maternal and reproductive health care units [ 16 ].…”
Section: Methodsmentioning
confidence: 99%
“…Whereas previous studies show a low knowledge and awareness of PCC among health workers in other countries such as Australia [40], New Zealand [12], Iran [41], and Ethiopia [39], our study shows that knowledge and awareness of PCC and its primary components among health workers at all levels are high and in line with those described by the WHO and CDC [2][3][4]. This has major implications of facilitating access and acceptability of PCC at the population level and can improve reproductive health outcomes when integrated with routine maternal and child health services.…”
Section: Discussionmentioning
confidence: 73%
“…Negative attitudes towards PCC and poor conviction of its importance were also noted [1,9]. Other studies have also shown that confusion about who should provide PCC [3,10,11], perception of lack of opportunity to provide PCC [12] and lack of motivation to provide PCC are barriers to provision by health care workers [13]. On the other hand, good knowledge and having a positive attitude towards PCC have been identified as facilitators of provision of PCC services by health care workers [1,10,11,14].…”
mentioning
confidence: 94%
“…In addition, reproductive health planning and its benefits including financial readiness of the couple was mentioned. In comparison, studies among health workers in other places such as Australia [21], New Zealand [8], Iran [22] and Ethiopia [20] reported low knowledge and awareness of PCC, although these studies were quantitative in nature. On the other hand, a qualitative study among physicians in rural Pennsylvania, US showed awareness of the need for pregnancy planning and the importance of optimal maternal health prior to pregnancy and described its necessity for women with high risk conditions like hypertension, seizure disorder, depression and diabetes [6].…”
Section: Discussionmentioning
confidence: 93%
“…Negative attitudes towards PCC and poor conviction of its importance were also noted [1,5]. Other studies have also shown that confusion about who should provide PCC [3,6,7], perception of lack of opportunity to provide PCC [8] and lack of motivation to provide PCC are barriers to provision by health care workers [9]. On the other hand, good knowledge and having a positive attitude towards PCC have been identified as facilitators of provision of PCC services by health care workers [1,6,7,10].…”
Section: Introductionmentioning
confidence: 94%